Effect of liquid organic fertilizer on growth and yield of rice varieties in rainfed field - Bayu Martedy Adji Saroyo; Iwan Sasli; Tatang Abdurrahman (JPBIO (Jurnal Pendidikan Biologi), 2023)
Rice is a superior crop that is cultivated and increased in productivity. Increasing rice productivity is done in an efficient way, especially in rainfed land, namely the addition of Liquid Organic Fertilizer (LOF) and variety selection. The purpose of the study was to determine the effect of LOF, the effect of interaction between LOF and varieties on growth. This research is experimental using the RAK split plot method consisting of two factors. The first factor is LOF consisting of fermented banana stump, coconut fiber, bamboo shoots and maja fruit as the main plot with 2 levels of treatment, namely without LOF and with LOF. The second factor is rice varieties as subplots with 5 treatment levels. Combination of 2 levels of LOF and 5 levels of rice varieties. The number of sapling, net assimilation rate, and relative growth rate of rice with LOF were significantly different from those without LOF. The provision of LOF on the Inpari Sidenuk variety has the highest average number of sapling, which is 18 stems and is significantly different from the treatment without LOF which has an average number of tillers of 15.40 stems. So that the provision of LOF provides growth on rainfed land.